Development of a scientific literacy test instrument on the immune system - Pensa, Yulita; Ningsih , Kurnia; Panjaitan, Ruqiah Ganda Putri (JURNAL BIOEDUKATIKA, 2024)
This research aims to develop a scientific literacy test instrument on immune system material. Borg & Gall research and development modified by Sugiyono is the research methodology used.. The questions developed were 25 multiple-choice questions created using 9 indicators from the TOSLS instrument developed by Gormally, Brickman, and Lutz. The questions were tested on 75 class Xl students at SMA Negeri 7 Pontianak who were selected using a simple random sampling technique. Rasch model analysis was used to analyze the questions. The content validity results stated that it was valid (0.92) and had good interrater reliability (0.88). Item validity (item fit) shows 25 valid. Reliability shows the Cronbach's Alpha category is bad (0.50), the person reliability category is weak (0.46), the item reliability value is very good (0.94). The person separation value is 2 and the item separation value is 6. The difficulty of the questions (item measure) demonstrates Six questions are extremely difficult, six questions are difficult, eight questions are easy, and five questions are extremely easy. From the results of the analysis, It can be conclude that the questions are valid and reliable even though there are questions that need to be revised.Keywords: Scientific Literacy test instrument, 9 TOSLS indicators, Rasch Analysis